Non-severe hypoglycemia in type 1 diabetes: a randomized crossover trial comparing two quantities of oral carbohydrates at different insulin-induced hypoglycemia ranges - Taleb, Nadine; Gingras, Véronique; Cheng, Ran; Parent, Valérie; Messier, Virginie; Bovan, Danijela; Shohoudi, Azadeh; Brazeau, Anne-Sophie; Rabasa-Lhoret, Rémi (Frontiers in Endocrinology, 2023)
AIMS Non-severe hypoglycemia (NS-H) is challenging for people living with type 1 diabetes (PWT1D) and often results from relative iatrogenic hyper-insulinemia. Current guidelines recommend a one-size-fits-all approach of 15-20 g simple carbohydrates (CHO) every 15 min regardless of the triggering conditions of the NS-H event. We aimed to test different amounts of CHO to treat insulin induced NS-H at various glucose ranges. METHODS Randomized four-way crossover trial in PWT1D, testing NS-H treatment outcomes with 16 g vs. 32 g CHO at two plasma glucose (PG) ranges: A: 3.0-3.5 mmol/L and B:  3.0 mmol/L. Across all study arms, participants consumed additional 16g CHO if PG was still  3.0 mmol/L at 15 min and  4.0 mmol/L at 45 min post initial treatment. Subcutaneous insulin was used in a fasting state to induce NS-H. Participants had frequent venous sampling of PG, insulin and glucagon levels. RESULTS Participants (n=32; 56% females) were; mean (SD), 46.1(17.1) years old, had HbA1c at 54.0 (6.8 mmol/mol) (7.1% (0.9%)), diabetes duration of 27.5(17.0) years and 56% were insulin pump users. We compared NS-H correction parameters between 16 g vs. 32 g CHO for range A 3.0-3.5 mmol/L (n=32) and range B  3.0 mmol/L (n=29). Change in PG at 15 min for: A) 0.1(0.8) mmol/L vs. 0.6(0.9) mmol/L, p=0.02; B) 0.8(0.9) mmol/L vs. 0.8(1.0) mmol/L, p=1.0. Percentage of participants with corrected episodes at 15 min: A) 19% vs. 47%, p=0.09; B) 21% vs. 24%, p=1.0. A second treatment was necessary in A) 50% vs 15% participants p=0.001; B) 45% vs 34%, p=0.37. No statistically significant differences in insulin and glucagon parameters were observed. CONCLUSIONS NS-H, in context of hyper-insulinemia, is difficult to treat in PWT1D. Initial consumption of 32 g CHO revealed some advantages at the 3.0-3.5 mmol/L range. This was not reproduced at lower PG ranges since participants needed additional CHO regardless of the amount of initial consumption.